A Federal Anti-Scab Law for Canada? the Debate Over Bill C-257 - Savage, Larry; Butovsky, Jonah (Just Labour: A Canadian Journal of Work and Society, 2009)
This article reviews the arguments for and against adopting an anti-scab law and considers what impact such laws have on unions, businesses and individual workers. This article will then look at the constellation of players in today’s debate: governments, political parties, labour organizations, and the business community. The article will focus on the Canadian Labour Congress’ (CLC) unsuccessful campaign for a federal anti-scab law, in the form of bill C-257, to determine what, if anything, it says about labour politics and what lessons it provides for labour law reformers. (Excerpt from introduction)